Evaluation of Pharmaceutical Care Standard Implementation in Medan City Health Center, North Sumatra - H, Erviana N; W, Wiryanto; U, Harahap (Asian Journal of Pharmaceutical Research and Development, 2020)
Objectives: The implementation of Pharmaceutical Care Standards policies in health centers can be seen from the extent of suitability of human resources, facilities and infrastructure, management of medicines and consumable medical materials, clinical pharmacy care and quality control of pharmaceutical care. Inadequate implementation with the Pharmaceutical Care Standards policy will have a negative impact on service quality. This study aims to evaluate the implementation of Minister of Health Regulation No. 74 of 2016 concerning Pharmaceutical Care Standards in Medan City Health Center.Methods: This research is a cross sectional descriptive survey research. Data obtained from filling out questionnaire sheets and checklist sheets based on direct observation in outpatient health centers that have pharmacists and pharmacy technical staff at the pharmacy. The data obtained were analyzed using indicators and compared with literature standards. This research was conducted in July - October 2019.Results: The results showed that the total score of implementation of Pharmaceutical Care Standards in Medan City Health Center was 73-82 included in category II / moderate. Implementation has not yet fully met the standards, this is indicated by aspects of facilities and infrastructure; clinical pharmacy care have not been carried out effectively because it is related to the ratio between the number of patients with pharmacists and pharmaceutical technical personnel in the health center that is still not rational; and management of drugs and medical consumables. Assessment of the highest level of patient satisfaction is the Satisfaction category, as many as 77.89-97.87%.Conclusions: Implementation of Minister of Health Regulation No. 74 of 2016 concerning Pharmaceutical Care Standards in Medan City Health Center is included in the Medium Category. Factors affecting implementation include human resources and infrastructure. The level of patient satisfaction is Satisfied Category.